ANALISIS KOMPETENSI TENAGA PENJUAL DAN PERIKLANAN TERHADAPKEPUTUSAN PEMBELIAN MOBIL TOYOTA AGYA SERTA DAMPAKNYA PADA KESETIAN PELANGGAN TOYOTA - Gumilang, Inda - (Jurnal Manajemen Retail, 2022)
The purpose of this research is to find the influence of sales competence and advertising to purchase decision toyota agya and efect on customer loyalty (Study case at PT. PLAZA TOYOTA, Tendean, Pemuda, Kyai Tapa, Green Garden and Gading Serpong Branch). This research data collection use the quesioner spreed to responden. Population in this research is TOYOTA customer in PT. PLAZA TOYOTA area Jakarta).Sampling method used in this research is non-probability sampling, with purposive sampling technique. The number of samples in this study was 265 respondents. Instrument calibration is performed to test grain validity and reliability coefficient. The model used in this research is the model of causality or influence relationship. The hypothesis used in this research is to use the technique of Structural Equation Modeling (SEM). The results of this study conclude that sales competence variables have an influence on purchasing decisions of 4.92, while the value of advertising affects the purchase decision of 9.44. It can be concluded that the value of advertising is more influential on sales competence. Then, the value of sales competence to loyal customers of 0.03 and the value of advertising to loyal customers of 0.62. It can be concluded that the two variables have no significant effect on loyal customers toyota. While purchasing decisions have an effect on loyal customers of 2.60. When viewed in its entirety, which has the most influence on loyal customers is the purchase decision. Based on the results of this study can be concluded that in improving purchasing decisions required sales and advertising competence is good and interesting, and purchasing decisions were influenced by the number of loyal customers